How to teach about sustainable development in physical education? Examples from the perspectives of certified teachers in Sweden - Fröberg, Andreas; Wiklander, Petter; Baena-Morales, Salvador; Lundvall, Suzanne (Frontiers in Education, 2023)
Teachers have a vital role in educating and empowering students to become informed and active agents of change in promoting sustainable development (SD). Little is known what PE teachers teach about SD. The aim of the present study was to explore what certified compulsory school and uppersecondary school physical education (PE) teachers in Sweden teach about SD within their practice. An online survey was used to collect data about background information and what the PE teachers had taught about SD in PE. Data from 653 PE teachers was used and the teaching examples were analysed through thematic analysis. The analysis resulted in eight themes: Equality, inclusion, and norms, Exploring the local environment, Outdoor education and care of nature, Interdisciplinary projects, Picking waste and recycling, Sustainable bodies, Sustainable lifestyles, health and wellbeing, and Sustainable use of products and consumption. The findings suggest that PE can have distinct subject-specific contribution to aspects of the SD agenda, but also a role to empower students of how movement, exercise, and sport can be embedded within a broader ecological perspective. Furthermore, the described themes may open for research about what competences that are particularly relevant for PE teachers in the context of SD.